Study on Practical Measures for the Development of Korean Track and Field - Bang-Chool Kim; Sung-ho Kwon; Tai-woo Kim; Do-heung Lee (Korea Institute of Sport Science, 2022)
PURPOSE In this study, in-depth interviews were conducted with track-and-field athletes and leaders who participated in the Tokyo Olympics. The study aimed to present practical measures for the development of Korean track and field, which people at the forefront of Korean track and field thought. METHODS In-depth interviews were conducted using semi-structured questions for a total of five track-and-field national athletes and four track and field coaches. RESULTS A total of 39 subcategories and 104 concepts were derived with regard to four research questions: the process up to the Tokyo Olympics, the actual condition of Korean track and field, a comparison with track-and-field power nation, and practical measures for becoming track-and-field power nation. CONCLUSIONS Practical measures are needed to improve and develop the competitiveness of Korean track and field, which is expected to improve its competitiveness and help develop Korean track and field in the future.